2018
DOI: 10.1186/s12866-018-1284-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the gut-specific microbiome from field-captured tsetse flies, and its potential relevance to host trypanosome vector competence

Abstract: BackgroundThe tsetse fly (Glossina sp.) midgut is colonized by maternally transmitted and environmentally acquired bacteria. Additionally, the midgut serves as a niche in which pathogenic African trypanosomes reside within infected flies. Tsetse’s bacterial microbiota impacts many aspects of the fly’s physiology. However, little is known about the structure of tsetse’s midgut-associated bacterial communities as they relate to geographically distinct fly habitats in east Africa and their contributions to parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 53 publications
(80 reference statements)
0
23
0
Order By: Relevance
“…Also, no specimens of G. morsitans submorsitans (savannah group) and G. fuscipleuris (forest group) were captured. With regard to these two species, a recent study confirmed the presence of G. fuscipleuris [20]; by contrast, the small zone in the North-West (Turkana county) where G. morsitans submorsitans was historically reported [23] was not investigated, so its continued presence in Kenya cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, no specimens of G. morsitans submorsitans (savannah group) and G. fuscipleuris (forest group) were captured. With regard to these two species, a recent study confirmed the presence of G. fuscipleuris [20]; by contrast, the small zone in the North-West (Turkana county) where G. morsitans submorsitans was historically reported [23] was not investigated, so its continued presence in Kenya cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Eight species of tsetse fly are historically reported to be present in Kenya: G. brevipalpis; G. longipennis and G. fuscipleuris (fusca/forest group, subgenus Austenina); G. pallidipes; G. austeni; G. swynnertoni and G. morsitans submorsitans (morsitans/savannah group, subgenus Glossina (sensu stricto)); and G. fuscipes fuscipes (palpalis/riverine group, subgenus Nemorhina) [17,18]. With the exception of G. fuscipleuris and G. morsitans submorsitans, the presence of these species has been confirmed in a review of the scientific literature that covered the period 1990-2014 [19], and a more recent study also confirmed the presence of G. fuscipleuris [20]. Due to a combination of topographical, climatic, environmental and anthropogenic factors, the distribution of tsetse flies in Kenya is known to be fairly fragmented [21][22][23] In regard to AAT, the major trypanosome species affecting livestock in Kenya are Trypanosoma congolense, T. vivax, T. brucei and T. simiae.…”
Section: Introductionmentioning
confidence: 89%
“…This may prove beneficial because flies with a reduced life span could perish before trypanosomes are able to complete their 20–30 extrinsic incubation period [65]. A reduction in Sodalis density could be further beneficial because tsetse that house relatively low densities of the bacterium are less likely to be infected with trypanosomes than are individuals that house more of the symbiont [1923]. Thus, the trypanosome refractory phenotype presented by Kco_Z colonized tsetse may result in part from, or be enhanced by, the fact that they contain fewer Sodalis .…”
Section: Discussionmentioning
confidence: 99%
“…This structure is an important mediator of tsetse’s vector competence because it serves as a physical barrier that ingested parasites must traverse in order to successfully colonize the fly’s gut [17] and subsequently the salivary glands for transmission in saliva [18]. Sodalis’ impact on tsetse vector competency is less known, although studies suggest that a positive correlation exists between the prevalence and density of this bacterium and trypanosome infection prevalence [1923]. Like mosquitoes, tsetse’s gut also harbors a diverse population of bacteria obtained from the fly’s environment [1012].…”
Section: Introductionmentioning
confidence: 99%
“…Obligate symbionts are associated with nutrient provisioning as well, as demonstrated by the tsetse fly ( Glossina spp.) bacteria Wigglesworthia (Aksoy, Enterobacteriales: Erwiniaceae), which aids in the synthesis of B vitamins ( Wang et al 2013 , Griffith et al 2018 ) and the olive fly gut bacteria that assist in amino-acid provisioning to supplement the honeydew diet of their hosts ( Ben-Yosef et al 2010 ). Obligate nutrient provisioners are directly implicated in developmental success, as in Nardonella and Sodalis , which synthesize tyrosine that aids in durable exoskeleton construction in the herbivorous weevils Pachyrhynchus infernalis (Fairmaire, Coleoptera: Curculionidae) and Sitophilus spp., respectively ( Vigneron et al 2014 , Anbutsu et al 2017 ).…”
Section: Host Nutritionmentioning
confidence: 99%